Monolayer curvature stabilizes nanoscale raft domains in mixed lipid bilayers - Meinhardt, Sebastian (National Academy of Sciences, 2013)
According to the lipid raft hypothesis, biological lipid membranes are laterally heterogeneous and filled with nanoscale ordered “raft” domains, which are believed to play an important role for the organization of proteins in membranes. However, the mechanisms stabilizing such small rafts are not clear, and even their existence is sometimes questioned. Here, we report the observation of raft-like structures in a coarse-grained molecular model for multicomponent lipid bilayers. On small scales, our membranes demix into a liquid ordered (lo) phase and a liquid disordered (ld) phase. On large scales, phase separation is suppressed and gives way to a microemulsion-type state that contains nanometer-sized lo domains in an ld environment. Furthermore, we introduce a mechanism that generates rafts of finite size by a coupling between monolayer curvature and local composition. We show that mismatch between the spontaneous curvatures of monolayers in the lo and ld phases induces elastic interactions, which reduce the line tension between the lo and ld phases and can stabilize raft domains with a characteristic size of the order of a few nanometers. Our findings suggest that rafts in multicomponent bilayers might be closely related to the modulated ripple phase in one-component bilayers.